2003
DOI: 10.1515/crll.2003.010
|View full text |Cite
|
Sign up to set email alerts
|

On the 2-compact group DI(4)

Abstract: Besides the simple connected compact Lie groups there exists one further simple connected 2-compact group, constructed by Dwyer and Wilkerson, the group DI(4). The mod-2 cohomology of the associated classifying space BDI(4) realizes the rank 4 mod-2 Dickson invariants. We show that mod-2 cohomology determines the homotopy type of the space BDI(4) and that the maximal torus normalizer determines the isomorphism type of DI(4) as 2-compact group. We also calculate the set of homotopy classes of self maps of BDI(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…By construction, the restriction of Bψ q to the maximal torus of BSol(q ∞ ) is the map induced by x → x q , and hence this is an "Adams map" as defined by Notbohm [18]. In fact, by [18, Theorem 3.5], there is an Adams map from BDI(4) to itself, unique up to homotopy, of degree any 2-adic unit.…”
Section: Bdi(4)mentioning
confidence: 99%
“…By construction, the restriction of Bψ q to the maximal torus of BSol(q ∞ ) is the map induced by x → x q , and hence this is an "Adams map" as defined by Notbohm [18]. In fact, by [18, Theorem 3.5], there is an Adams map from BDI(4) to itself, unique up to homotopy, of degree any 2-adic unit.…”
Section: Bdi(4)mentioning
confidence: 99%
“…We state these properties without proof because either they can be found in the papers [7], [12], [4], [11] or they follow from straightforward computations that are left to the reader.…”
Section: The 2-compact Group G 3 and Its Maximal Torusmentioning
confidence: 99%
“…By [11,Proposition 3.3], the Adams operation Ψ q is an equivalence and therefore it induces an isomorphism of the algebra H * (BDI(4);…”
Section: The Bockstein Spectral Sequence For Bsol(q)mentioning
confidence: 99%
“…Soon after the experts became aware of the existence of self homotopy equivalences Ψ q : BDI(4) −→ BDI(4) for each odd prime power q, which are analogues of the unstable Adams operations on classifying spaces of compact Lie groups completed away from q. The first publish proof of this fact appeared in Notbohm's work [11]. Benson observed that Dwyer-Wilkerson's finite loop space DI(4) carries a 2-local structure closely related to Solomon's fusion systems.…”
Section: Introductionmentioning
confidence: 99%